Socio-Economic Situation of the Sverdlovsk Region in 1992: the First Year of “Shock Therapy” (according to Regional Statistics) - V. N. Mamyachenkov; M. I. Lvova (Научный диалог)
The socio-economic status of the Middle Urals in 1992, the first year of the implementation of the well-known program of “shock therapy” is considered. The selected topic seems relevant and of practical importance in the context of studying the mechanism for implementing large-scale reforms. The study was conducted on archival material. It is stated that in the history of modern Russia 1992 is a special period in its socio-economic significance. It is argued that the forms and methods of implementing “shock therapy” in Russia have left a deep, controversial and generally disturbing impression in the memory of most of its population. It is declared that the “shock therapy” of the 1990s in Russia in its essence was very similar to the new economic policy of the 1920s. It is shown that in the end of 1991 the USSR economy was in a state of deep systemic crisis and with virtually no reserves, on the verge of a complete collapse. It is noted that in 1992 the level of per capita consumption of food and non-food products by the majority of the population of the Sverdlovsk region continued to decrease. It is proved that the Sverdlovsk region in the Soviet period of the XX century was turned into a region with a hypertrophied industrial sector of the economy. It is concluded that the influence of long-term socio-economic mechanisms launched in 1992, will be experienced by the Russian society for a very long time.